Christian spirituality: concept, nature and meaning - Petrova, I. (Ukrai͏̈ns'ke relihijeznavstvo, 1999)
In religious studies, the issue of Christian spirituality is not sufficiently developed. In this regard, an interesting analysis of Christian spirituality in its connection with isihastic anthropology in the study of S. Khoruzhogo. However, the definition of Christian spirituality in this work is absent, although the term itself is used in the form of a synonym of isichasm, which is understood as its tradition and current. The philosopher asserts that the basis of Christian spirituality is the idea of ​​the deification of man, the acquisition of human nature by God. Therefore, Christian spirituality is the deification of man. This statement is an important methodological basis for the study of this phenomenon. The operational aspect of the spiritual experience of asceticism is emphasized, the latter is understood as the continuous work of self-transformation, autotransformation, mystical experience of transcendental and transcendental communication.